(3abg GddZg hSQ GdYQHjIs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s ((3eMeO Hf ehSi Hf eMeO Hf YjSi s)
(3ChdgG (B:s
(3QHfG BJfG ef dOfc QMeI QSGdI LYdgG CHh efUhQ YHO Gdedc Hf eMeO Hf ESeGYjd , ebOeI dcJGH abg GddZI hSQ GdYQHjI s
(3BNQgG (B:s
(3aUd ai JbSje GdRjGOI , CbeQ GdgdGd QGY GdWYGe , ef GdQjY , hgh GdfRd Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GddZIs